Soil moisture partitioning strategies in blowouts in the Hulunbeier grassland and response to rainfall - Bao, Zhixin; Yuan, Limin; Meng, Zhongju; Zhang, Ezhen; Zhu, Lei; Liu, Jinwang (Frontiers in Environmental Science, 2025)
IntroductionSoil moisture and soil water retention capacity are key influencing factors for the normal growth and development of vegetation. Understanding the dynamic change characteristics of soil moisture in blowouts and soil water retention capacity is of great significance for the management of blowouts.MethodsThis study employs drying and in situ monitoring methods to select typical blowouts in different regions (sand pits, fringe zones, sand accumulation zones, and sand-grass transition zones) on the Hulunbuir Grassland. A large area of natural grassland surrounding these regions was chosen as the control (CK). Soil moisture at depths of 20, 40, 60, 100 and 200 cm below the surface was measured along the soil profile using the ECH2O-10HS soil moisture automatic monitoring instrument. The HOBO-RG3-M self-recording rain gauge was used to monitor rainfall. Soil water storage, coefficient of variation, and Pearson’s correlation coefficient were calculated to study the differences in soil moisture and the dynamic change regularity in soil moisture under different rainfall conditions. This research provides important theoretical support for the soil moisture distribution and vegetation restoration in the blowouts of the Hulunbuir Grassland.Results and discussionThe volumetric water content of the soil in the blowouts was 15.95%, the volumetric soil water content in different parts of the soil varied from low to high as follows: sand pit-I < sand-grass transition zone-IV < fringe zone-II < CK < sand accumulation zone-III. The soil volumetric water content of the 0–40 cm soil layer of the blowout was higher than 17.47%, and the soil volumetric water content of the 40–200 cm soil layer ranged from 12.13% to 17.47%. The volumetric water content of soil in various parts of the blowouts under different rainfall amounts had significant differences, with rainstorms and heavy rainfall effectively recharging the blowouts to a depth of 200 cm, and the blowouts responded strongly to heavy rainfall (71.5 mm). A gradual recovery of the pre-rainfall volumetric soil moisture content was seen approximately a week after rainstorms. The water retention and storage capacity of blowout soils was significantly higher than that of CK, the soil water storage capacity of different zones ranked in descending order as the sand accumulation zone (1875.38 mm) > edge zone (1373.22 mm) > CK (1188.36 mm) > sand pit (1000.39 mm) > sand–grass transition zone (803.90 mm). The correlation coefficient of sand pits and sand cover was 0.5612, and that of sand accumulation zones and sand cover was 0.5845, which confirmed that sand cover enhanced the water retention capacity of the localized area of blowouts (sand accumulation zones).